Gender Discrimination in Novel SOLD (2006) by Patricia MCCormick - Riri Anggraini Putri; Delvi Wahyuni (Universitas Negeri Padang, 2020)
AbstractThis thesis is an analysis of a novel written by Patricia McCormick entitled Sold (2006). This analysis looks at the gender discrimination that is experienced by women who are victims of gender discrimination acts. This analysis is related to the feminist approach and the concept of gender discrimination by Simone de Beauvoir. The analysis focuses on the issue of gender discrimination. The aim of this analysis is to what extent the character, conflict (plot), setting and stage direction contribute to reveal the issue of gender discrimination. This analysis also depends a lot on the narator to determine which parts of the novel are used as the data. The result of the study shows that Lakhsmi experienced gender discrimination such as marginalization, subordination, stereotype, violence and double burden.